Anionic chiral tridentate N-donor pincer ligands in asymmetric catalysis - Deng, Qing-Hai; Melen, Rebecca L.; Gade, Lutz H. (Accounts of chemical research, 2014)
ConspectusTridentate monoanionic ligands known as “pincers” have gained a prominent place as ligands for transition metals and, more recently, for main-group metals and lanthanides. They have been widely employed as ancillary ligands for metal complexes studied inter alia in bond activation steps relevant to catalytic processes. The central formally anionic aryl or heteroaryl unit acts as an “anchor” in the coordination to the metal, which kinetically stabilizes the resulting complexes. Their stability, activity, and reactivity can be tuned by subtle modifications of substitution patterns on the pincer ligand or by modifying the donor atoms. The challenges in pincer ligand design for enantioselective catalysis have been met by their assembly from rigid heterocycles and chiral ligating units in the “wingtip” positions, which generally contain the stereochemical information. The resulting well-defined geometry and shape of the reactive sector of the molecular catalyst favor orientational control of the substrates. On the other hand, the kinetic stability allows reduced catalyst loadings.Recently, a new generation of tridentate anionic N∧N∧N pincer ligands has been developed which give rise to highly enantioselective transformations. Their applications in asymmetric catalysis have focused primarily on the asymmetric Nozaki-Hiyama-Kishi coupling of aldehydes with halogenated hydrocarbons as well as Lewis acid catalysis involving enantioselective electrophilic attack onto metal-activated β-keto esters, oxindoles, and related substrates. These include highly selective protocols for Friedel-Crafts alkylations with Michael acceptors, electrophilic fluorinations, trifluoromethylations, azidations, and alkylations and subsequent transformations. Increasingly, these stereodirecting ligands are being employed in other types of transformations, including hydrosilylations, cyclopropanations, and epoxidations. The stability and well-defined nature of the molecular catalysts have made them attractive targets for mechanistic studies into a wide range of these transformations, thus providing the type of insight required for a more rational approach to catalyst development. This Account reviews work performed by us and other groups in the field and places it into perspective in relation to general research efforts in enantioselective catalysis.
Gesehen am 17.07.2020